Assessment of Physical Fitness in Medical Students - Chaudhary, Sailesh; Khadka, Rita; Pandey, Karishma Rajbhandari; Paudel, Bishnu Hari; Shah, Gaurav Jung; Chaudhary, Hiramani Prasad (Journal of Nepalgunj Medical College, 2022)
Introduction: Physical activity promotes cerebral blood flow during cognitive tasks and possibly enhances performance. It is relevant to find relationship between post exercise recovery heart rate (RHR) and resting pulse rate in medical students.Aims: To assess physical fitness in medical students.Methods: In this cross-sectional study, 57 consenting healthy medical students, age 1730 years, underwent 3-Minutes Step Test to assess their physical fitness. Students were divided into four fitness groups based on RHR; good (n=9, RHR=50-84 bpm), satisfactory (n=17, RHR=88-100 bpm), poor (n=12, RHR=102-107 bpm), and very poor (n= 19, RHR=111-157 bpm) groups. The groups were compared using one-way ANOVA. A p